Learning to perceptually organize speech signals in native fashion - Nittrouer, Susan (Acoustical Society of America, 2010)
The ability to recognize speech involves sensory, perceptual, and cognitive processes. For much of the history of speech perception research, investigators have focused on the first and third of these, asking how much and what kinds of sensory information are used by normal and impaired listeners, as well as how effective amounts of that information are altered by “top-down” cognitive processes. This experiment focused on perceptual processes, asking what accounts for how the sensory information in the speech signal gets organized. Two types of speech signals processed to remove properties that could be considered traditional acoustic cues (amplitude envelopes and sine wave replicas) were presented to 100 listeners in five groups: native English-speaking (L1) adults, 7-, 5-, and 3-year-olds, and native Mandarin-speaking adults who were excellent second-language (L2) users of English. The L2 adults performed more poorly than L1 adults with both kinds of signals. Children performed more poorly than L1 adults but showed disproportionately better performance for the sine waves than for the amplitude envelopes compared to both groups of adults. Sentence context had similar effects across groups, so variability in recognition was attributed to differences in perceptual organization of the sensory information, presumed to arise from native language experience.